Factors contributing to teenage pregnancy in the Capricorn district of the Limpopo Province - Mothiba, Tebogo M.; Maputle, Maria S. (My University, 2012)
Teenage pregnancy refers to pregnancy of a woman of less than 19 years. It is found commonly amongst young people who have been disadvantaged and have poor expectations with regard to either their education or job market. Adolescents may lack knowledge of access to conventional methods of preventing pregnancy, as they may be afraid to seek such information. The study purpose was to identify factors contributing to teenage pregnancy in one village in the Capricorn District of the Limpopo Province. A quantitative descriptive research approach was chosen. Population consisted of all pregnant teenagers attending antenatal care during June to August 2007 at one clinic in the Capricorn District of the Limpopo Province. Simple random probability sampling was used to include 100 pregnant teenagers who satisfied the inclusion criteria. Data were collected through structured self-administered questionnaires. Descriptive statistical data analysis was used. Ethical considerations were ensured. Findings were classified as demographic data where 24% of the respondents were aged between 15–16 years and 76% were aged between 17–19 years. Findings further revealed that 60% of the respondents started to engage in sex at 13–15 years; 48% of the teenagers’ partners were 21 years and above, 44% depended on a single parents’ income; 20% father’s income, 16% received a social grant and 8% lived on the pension fund of the grandparents. Pregnancy prevention strategies were recommended based on the results. The strategies focused on reproductive health services, male involvement and adult-teenager communication programmes.
Original research Journal article, 5 p. Published in Curationis 35(1), Metadata creation was based on submitted article.
Keywords: Teenagers; Teenage pregnancy -- South Africa -- Limpopo; Pregnancy